Accessibility Legal Aid In Realize Fair Teacher Protection - Aman Serah, Yenny; Setiawati, Rini; Sirait, Resmaya Agnesia Mutiara; Marina, Liza; Astono, Agustinus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Rule law, in essence, has accommodated giving teacher protection; however, the reality of teacher criminalization still happen. This study aims for uncovering the challenge of fulfillment right accessibility help law as a form of fair teacher protection. The method used was socio-juridical with an approach qualitative, through tool-collecting data questionnaires, interviews, and discussions focused on teacher respondents, unit education, teacher organizations, and agencies that handle education and protection child. Research results showed that not yet a clear existence mechanism for giving protection law impacted teachers’ accessibility and help the law to the teacher yet running optimally. By substantive mechanism gift help law to the teacher, they yet accommodated. So that when occurring, problems between teachers and students were solved with various actions, of which 48.57% stated through deliberation; however, there was take action alone with each other dropping on social media. Even the teachers who experienced criminalization no get help law. In research, this uncovers required something institutional level idealized area as a Legal Service and Teacher Protection Unit (LSTPU) can be made receptacle fulfillment accessibility help law in realizing fair teacher protection. Researchers recommend that the formation of LSTPU institutions through policy Required Regional Regulations (RRG) conducted assessment continued